Acethylcholinesterase Levels of Aedes aegypti Larvae after Exposure to The Pandanus amaryllifolius Leaf Extracts - Lidya Anin; Hebert Adrianto; Hanna Tabita Hasianna Silitonga; Setyarina Indrasari; Kartika Buana Sari (Magna Medika)
Background:  Dengue fever is a disease transmitted by Ae. aegypti. Controlling mosquitoes can use temephos. Temephos larvicides act primarily on the enzyme acetylcholinesterase (AChE) by inhibiting this enzyme. Temephos has drawbacks due to its high risk of resistance, so larvicides from natural ingredients such as pandan leaf extract (P. amaryllifolius) can be an alternative. The mechanism of action of P. amaryllifolius larvicide is still unclear. Objective: This study aims to ascertain how LC85 pandan leaf methanol extract affects AChE levels in Ae. aegypti. Methods: This is an actual experiment design with only a post-test control group research design. Tests were conducted by treating mosquito larvae with P. amaryllifolius LC85 extract, aquades, and temephos for 24 hours and measuring AChE levels with an ELISA Reader. Results: The results showed that the AChE enzyme levels of P. amaryllifolius LC85 extract had an average AChE enzyme level of 147.19 + 70.87 units/l. The AChE enzyme levels of larvae exposed to P. amaryllifolius LC85, aquades, and temephos significantly differed (p <0.05). Conclusion: P. amaryllifolius has potential as a larvicidal, with a mechanism of action as a neurotoxin.